2011
DOI: 10.3109/09553002.2011.556178
|View full text |Cite
|
Sign up to set email alerts
|

Specific issues in small animal dosimetry and irradiator calibration

Abstract: Purpose In response to the increased risk of radiological terrorist attack, a network of Centers for Medical Countermeasures against Radiation (CMCR) has been established in the United States, focusing on evaluating animal model responses to uniform, relatively homogenous whole- or partial-body radiation exposures at relatively high dose rates. The success of such studies is dependent not only on robust animal models but on accurate and reproducible dosimetry within and across CMCR. To address this issue, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 36 publications
1
66
0
Order By: Relevance
“…These systems have high-resolution imaging capabilities, technically precise robotic movements, and energies scaled to match the small animal geometries. Concurrent to the rise in popularity of these irradiation systems has been a call for accurate and standardized dosimetry within small animal models (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems have high-resolution imaging capabilities, technically precise robotic movements, and energies scaled to match the small animal geometries. Concurrent to the rise in popularity of these irradiation systems has been a call for accurate and standardized dosimetry within small animal models (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…The widespread usage of small animal models has spurred development of physical phantoms of mice as well. Simple mouse phantoms, which are often no more than a tube with slots for the insertion of a detector, are prevalent for dosimetry (3,5,6,21). The rise in popularity and capability of rapid prototyping tools, such as 3D printers and computer controlled milling machines, has allowed for a new generation of physical mouse phantoms with intricate features that closely mimic the animals they represent.…”
Section: Introductionmentioning
confidence: 99%
“…As Yoshizumi et al 8 have reported, "Physics support is needed, but is often the weakest link in the small animal dosimetry chain." The current status of irradiator physics, especially orthovoltage x-ray units, calls for more recognition of the importance of having a rigorous irradiator QA program and advancement in related technological and scientific research.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Cycle Analysis, RT-PCR genomic expression analysis, immunohistochemistry, and irradiation technique followed standard experimental methodology (32, 33). A detailed breakdown can be found in the Supplementary Materials and Methods section.…”
Section: Methodsmentioning
confidence: 99%